STRATEGI PENGEMBANGAN EKOWISATA BERBASIS EKONOMI LOKAL DALAM RANGKA PROGRAM PENGENTASAN KEMISKINAN DI WILAYAH KABUPATEN MALANG - Satria, Dias (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
In the era of sustainable development, alternative and sustainable tourism havebecome a great concern for local government. Sempu Island which is located inKabupaten Malang is one of the interesting cases on how the Ecotourism conceptcould be combined to the local economic development and conservation issues. Theaims of this paper are to gather information about the picture of Ecotourism practicesin Sempu Island. Furthermore, it will formulate the strategic way to make ecotourismwork well to the development of the local society.Keywords: Sustainable development, ecotourism, Sempu Island and local economy.